Geologically recent rearrangements in central Amazonian river network and their importance for the riverine barrier hypothesis - Ruokolainen Kalle; Moulatlet Gabriel M.; Zuquim Gabriela; Hoorn Carina; Tuomisto Hanna (International Biogeography Society, 2022)
The riverine barrier hypothesis is a central concept in Amazonian biogeography. It states that large rivers limit species distributions and trigger vicariant speciation. Although the hypothesis has explanatory power, many recent biogeographical observations addressing it have produced conflicting results. We propose that the controversies arise because tributary arrangements in the Amazon river system have changed in geologically recent times, such that large tracts of forest that were on the same side of a river at one time got separated to different sides at another. Based on topographical data and sediment dating, we map about 20 major avulsion and river capture events that have rearranged the river network in central Amazonia during the late Pleistocene and Holocene. We identify areas where past riverine barrier effects might still linger in the absence of a major river, as well as areas where such effects may not yet have accumulated across an existing river. These results call for a reinterpretation of previous biogeographical studies and a reorientation of future works to take into account the idiosyncratic histories of individual rivers.